Women's non-farm employment and household dietary quality in rural China: evidence from a national rural health perspective - Yuan Gao; Gangyi Wang; Xiaochen Zhang (Frontiers in Public Health, 2026)
Background Improving dietary quality and reducing nutrition-related inequalities remain important public health challenges in rural populations. Women often play central roles in household food purchasing, meal preparation, and resource allocation, suggesting that women's employment transitions may be closely linked to household nutritional outcomes. This study examines the association between married women's non-farm employment and household dietary quality in rural China and explores potential pathways underlying this relationship. Methods Data were drawn from 1,723 rural households in the China Rural Revitalization Survey (CRRS). Household dietary quality was assessed using the China Dietary Balance Index-22 (DBI-22), including the High Bound Score (HBS), Low Bound Score (LBS), and Diet Quality Distance (DQD), which capture excessive intake, insufficient intake, and overall dietary imbalance, respectively. Regression models, instrumental variable estimation, conditional mixed process estimation, propensity score matching, sensitivity analyses, subgroup analyses, and pathway analyses were used to examine the relationship between married women's non-farm employment and household dietary quality. Results Married women's non-farm employment was significantly associated with better household dietary quality. Specifically, women's employment was associated with lower LBS and DQD, indicating reduced insufficient dietary intake and overall dietary imbalance, while no significant association was observed with HBS. The findings remained stable across sensitivity analyses, instrumental variable estimation, and propensity score matching. Pathway analyses suggest that the association may operate through increased household income, improved intra-household resource allocation, and changes in food consumption structure. Subgroup analyses further showed that the association was more pronounced among households with stronger nutritional demands, lower income levels, and greater market constraints. Conclusion Married women's non-farm employment is an important social determinant of household nutritional welfare in rural China. Promoting gender-inclusive employment opportunities may contribute to improving dietary quality and reducing nutrition-related inequalities among rural populations.